Struktur Dan Fungsi Sosial Cerita Legenda Alam Gaib Urang Bunian Gunung Talang Masyarakat Nagari Air Batumbuk Kecamatan Gunung Talang Kabupaten Solok - Rahman, Hidayatul; Hasanuddin WS, Hasanuddin WS (Universitas Negeri Padang, 2024)
This study aims to (1) the structure of the story of the Legend of the Invisible Nature of the Urang Bunian Gunung Talang community in Nagari Air Batumbuk, Gunung Talang District, Solok Regency; and (2) the social function of this legend within the same community. This study employs a qualitative approach using descriptive methods. The focus of this research is the legendary story of the supernatural realm of the Urang Bunian in the Nagari Air Batumbuk community, Gunung Talang District, Solok Regency. Data were collected through recorded interviews and direct observation. The collected data were then analyzed in several stages: (1) data inventory (recording); (2) classification and analysis of the data; (3) concluding the results of the data classification and analysis; and (4) reporting the findings. Based on the results of the data analysis, the following were found: (1) the story structure of the legend of the supernatural realm of the Urang Bunian in the Nagari Air Batumbuk community includes: (a) the main character, the Urang Bunian; (b) the plot, which is divided into three stages: initial, middle, and final; (c) the setting, which encompasses place, time, and social context; and (d) the mandate to always maintain ethics and manners when entering the forest, as well as to protect the surrounding natural environment; and (2) the social functions of the Urang Bunian legend include education, inheritance, and identity.